Measurement of C-Organic Content in Sediment as an Indicator of Carbon Absorption Potential in the Bonto Bahari Mangrove Ecosystem, Maros Regency - Herawati, Sari; Rukminasari, Nita; Yunus, Budiman; Alam, Jamaluddin Fitrah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Mangrove ecosystems play an important role in mitigating global warming through their ability to absorb and store carbon in biomass and sediment. This research analyzes the organic carbon content and carbon sequestration potential in mangrove sediments in Bonto Bahari, Maros Regency, South Sulawesi. Using purposive sampling method, sediment samples were taken from 9 points with 5 different depths (0-50 cm) and analyzed using the Loss on Ignition (LOI) method. The results showed very low bulk density values (0.01-0.02 g/cm³) with the highest value at a depth of 20-30 cm. Carbon concentrations were relatively uniform (1.5-2.0%) at all depths with the highest concentration at a depth of 40-50 cm (1.93%). The highest carbon content was found at a depth of 40-50 cm (100.667 tons/ha) with carbon sequestration reaching 516.958 tons/ha, while the lowest value was at a depth of 0-10 cm (24.60 tons/ha). There were significant differences (p<0.05) in carbon content and sequestration between depths of 0-10 cm and 20-30 cm. This research reveals that deeper sediment layers play an important role in carbon storage in mangrove ecosystems, providing significant implications for sustainable mangrove management and local ecosystem-based climate change mitigation efforts